Graduate Teacher Education Students Use and Evaluate ChatGPT as an Essay-Writing Tool - Picciano, Anthony G (Online Learning, 2024)
Artificial intelligence (AI) has been evolving since the mid-20th Century when luminaries such as Alan Turing, Herbert Simon and Marvin Minsky began developing rudimentary AI applications. For decades, AI programs remained pretty much in the realm of computer science and experimental game playing. This changed radically in the 2020s when commercial vendors such as OpenAI and Google developed generative AI programs (ChatGPT) and (Bard) using large, language modelling (LLM). As a result, generative AI is now being considered for use in all walks of life including education. In Spring 2023, when ChatGPT burst into the public psyche, twenty-five education students in the author’s graduate seminar were invited to participate in a qualitative study using ChatGPT as a tool for completing an essay assignment. Fifteen (N=15) accepted the offer. The purpose in doing this was to give students in this seminar the opportunity to use ChatGPT in a supportive environment and to collect qualitative data from them on their experiences using ChatGPT. All of these students have master’s degrees in education and experience as teachers in New York City schools. Their training and experience give them keen insights into pedagogical practice making them ideally suited to evaluate ChatGPT as an instructional tool. This article reports on the results of this study. Keywords: Artificial Intelligence, AI, ChatGPT, Graduate Teacher Education, Qualitative Research